The Principal's Communication Style In Motivating Teachers' Work At Sma Brigjend Katamso II Medan - Winda Sihotang; Nathanael Sitanggang; Joharis Lubis (International Journal of Educational Research & Social Sciences, 2021)
This study describes the principal's communication style and the factors driving the principal's communication at Brigjend Katamso II Senior High School Medan. The purpose of this study was to determine the principal's communication style in motivating the work of teachers at (Senior High School) SMA Brigjend Katamso II Medan City. This study uses data collection techniques through in-depth interviews, observation, and documentation with informants (teachers and staff employees). The results of the study prove that the communication style used by the principal is a controlling style. The principal in motivating the work of teachers plays a multifunctional role. In providing work motivation, the principal uses Indonesian and uses casual language in informal activities. The relationship between the principal and the teacher is harmonious which can motivate the work of the teacher and the principal obstacle in motivating the work of the teacher is that he is a little slow in conveying information.